Early detection of cardiotoxicity by 2D and 3D deformation imaging in patients receiving chemotherapy - Tarr, Adrienn; Stoebe, Stephan; Tuennemann, Jan; Baka, Zsuzsanna; Pfeiffer, Dietrich; Varga, Albert; Hagendorff, Andreas (Echo research and practice, 2015)
The aim of the present study was to find out whether early cardiac changes in patients receiving chemotherapy can be detected by the conventional and deformation parameters of 2D and 3D echocardiography. Twenty-five healthy subjects with normal regional left ventricular function (group 1) and 25 patients receiving chemotherapy (group 2) underwent 2D and 3D transthoracic echocardiography (Toshiba Artida Medical System). All patients (group 2) were examined before and during cardiotoxic chemotherapy at a 3-month follow-up. Left ventricular volumes, ejection fraction, muscle mass, global longitudinal, global radial, global circumferential strain, and rotation were analyzed with 2D and 3D echocardiography, while twist and time-to-peak-intervals were analyzed with 3D echocardiography. For left ventricular volumes and muscle mass, no significant differences were seen between the two study groups (P<0.05). According to our results, myocardial dysfunction induced by cardiotoxic chemotherapy can be detected by 2D global radial strain. Detecting myocardial dysfunction by global longitudinal and circumferential strain requires more than 3 months follow-up. Changes in rotation, twist or time-to-peak intervals could not be verified at the 3-month follow-up in the present study. 2D global radial strain seems to be the most sensitive and robust parameter to detect early myocardial damage during chemotherapy. 3D echocardiography is not yet an established method to detect myocardial damage in clinical practice due to lower spatial and temporal resolution.